Produktivitas Sapi Bali pada SistemPenggembalaan di Kabupaten Bombana - Rauf, A.; Priyanto, R.; Karti, P. D. M. H. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Beef cattle in Bombana district are commonly raised extensively on community grassland. This research aimed to assess the performance of Bali cattle on grazing system that was reconditioned with locally-based feed supplement. The research was conducted during the dry season from Juni-Oktober 2014. The data collected were analysed descriptively and followed with  analysis of variance (ANOVA). The results showed that the management of Bali cattle was carried out in full day grazing system.Carrying capacityat sub districtMata Usu and Lantari Jaya was 1.15 AU/ha/year and 0.66 AU/ha/year. Daily weight gain  of grazing cattle for both, without feed suflement, and suflemented with rise brand, and cocoa pod were 0.148 kg/head/ day, 0.207 kg/head/day; and 0.138 kg/head/day respectively. The cows calving rate was 77.60%  and mortality  rate was  8.14% . in total, calve mortality rate was 17.88%. In conclusion, the productivity of grazing catle in Bombana distric was relatively beetween low to moderat. Supplementation of rice brand, slighty improved the performance of grazing cattle in the dry season.